Understanding MOOCs (Massive Open Online Courses) and its Pedagogy to Use it as a Potential Solution for Learning - Rathee, Dr. Neeru; Bhardwaj, Karuna (Voices of Teachers and Teacher Educators, 2020)
Through the ages, the will of providing low cost and effective education has existed but we were unable to find a potential solution for it. MOOC can be a potential solution for free education but there is to understand its nature, characteristics, types and pedagogy. There are two types of MOOC -C-MOOC and X-MOOC. C-MOOC based on the theory of connectivism and X-MOOC based on behaviourist model. X-MOOC provide a structured and centralized way of delivering the content. Both types of MOOC have their strength and limitations. MOOC is becoming more and more popular with time as more than 110 million learners join MOOC but according to the Harvard University, only 6 per cent of the total candidates complete the course which shows that there is a need to explore the ideas to use it effectively. MOOC is a good source of knowledge, but we need to understand the pedagogy behind different MOOC so that it helps the teachers and learners to use it effectively and efficiently. This paper is based on the analysis of the available literature and research conducted on the effectiveness of MOOC programme in a blended mode for teacher education course by the researcher. This paper tries to find a potential solution to use MOOC in the best way for learning. It will help the learners to choose different MOOCs according to their needs, learning styles by making them understand the pedagogic difference between the types of MOOCs.